Distribuição regional das receitas e despesas do Governo Central no II Reinado, 1844-1889 - Villela, André (Estudos Econômicos (São Paulo), 2007)
One of the most striking features of Brazilian political history in the second half of the nineteenth century was the extent of centralization of power, decisions and economic resources in Rio de Janeiro, seat of the central government. This primacy of the imperial over the provincial and local governments was revealed in both its attributions and the fiscal resources it commanded. The article aims to measure the relative contributions of the provinces of the so-called North and South of the Empire to the total amount of receipts and expenditures of the central government. The results indicate a disproportionate contribution of the Northern provinces to overall collection, thus confirming contemporaries' views and earlier research on this issue.